Praktik Kolaborasi Perawat-Dokter dan Faktor yang Memengaruhinya - Wiwin Martiningsih (Universitas Airlangga, 2011)
Introduction: Collaboration is basically discuss about togetherness, cooperation, sharing tasks, equality, responsibility, and accountability. Purpose of this research was to learn the collaboration practice beetwen nurses and physician and the factors affecting. Method: Design of this research was correlational and comparational study, and population were the physician who work in Ngudi Waluyo Blitar hospitals, intensive cooperation with the nurse in the room, not holding structural positions and not studying, there are 19 peoples taken by total population and nurses who work in Ngudi Waluyo hospitals, not holding structural positions (Head of Division or Head of Section), having relationship with the physician and the samples were 31 peoples taken by probability proportional to size (PPS). Methods of data collection by giving questionnaire about the characteristics of respondents (nurses and physician) and practice of collaboration scale. Data characteristics and attitudes of nurses and physicians about the practice of collaboration is analyzed with descriptive statistics, to know the differences between nurses and physicians attitude using mann whitney u test. To know affecting characteristic with nurses and physician attitude by multivariate analysis. Result: Results of mann whitney test p value is 0.611, which means that there is no difference between nurses and physician attitude in practice collaboration, and result of multivariate analysis the influence of nurse characteristics (age, education, functional potition, length of working) with attitude are 0.460 or 46%, while 54% influenced by other factors, and the influence of physician characteristics (age, education, length of working) with attitude are 0.435 or 43.5%, while 56.5% influenced by other factors. Discussion: Further need to study other factors that influence and research by observation the impact of collaboration between the nurse with physician on the service quality.